1988
DOI: 10.1159/000185036
|View full text |Cite
|
Sign up to set email alerts
|

Medical Renal Disease in the Elderly in a Southern Indian Hospital

Abstract: A review of 85 patients aged 60 years or more, treated in a southern Indian hospital for conditions requiring renal biopsy, showed that diffuse poliferative glomerulonephritis was the most frequent diagnosis, being present in 24 cases of whom 11 had elevated serum streptococcal antibody titres. Infections were also important in 2 patients with amyloidosis secondary to tuberculosis, in 3 patients with acute tubular necrosis following infectious gastroenteritis and in a patient with acute pyaemic interstitial ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Recent reports have indicated that a wide variety of primary and secondary renal diseases occur in the older population 1 – 4 . A spectrum of glomerular, vascular, and interstitial disorders has been described and serves to underline the emerging notion that seeking a biopsy diagnosis is worthwhile in many cases.…”
mentioning
confidence: 99%
“…Recent reports have indicated that a wide variety of primary and secondary renal diseases occur in the older population 1 – 4 . A spectrum of glomerular, vascular, and interstitial disorders has been described and serves to underline the emerging notion that seeking a biopsy diagnosis is worthwhile in many cases.…”
mentioning
confidence: 99%